1983
DOI: 10.1042/cs0650143
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cardioselective and Non-Selective β-Adrenoceptor Blockade on the Hypokalaemic and Cardiovascular Responses to Adrenomedullary Hormones in Man

Abstract: Adrenaline was infused intravenously in nine normal volunteers to plasma concentrations similar to those found after myocardial infarction. This study was undertaken on three occasions after 5 days' treatment with placebo or the beta-adrenoceptor antagonists, atenolol or timolol. Adrenaline increased the systolic pressure by 11 mmHg, decreased the diastolic pressure by 14 mmHg, and increased the heart rate by 7 beats/min. These changes were prevented by atenolol. However, after timolol the diastolic pressure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Epinephrine infusion lengthens QTc interval in normal participants (34), predominantly through a ␤-adrenoceptor-mediated process, whereby the cardiac action potential is prolonged by delayed inactivation of inward calcium currents (35). In this study, we observed a relationship, albeit weak, between the magnitude of the hypoglycemic epinephrine response and the degree of QTc lengthening.…”
Section: Discussionmentioning
confidence: 53%
“…Epinephrine infusion lengthens QTc interval in normal participants (34), predominantly through a ␤-adrenoceptor-mediated process, whereby the cardiac action potential is prolonged by delayed inactivation of inward calcium currents (35). In this study, we observed a relationship, albeit weak, between the magnitude of the hypoglycemic epinephrine response and the degree of QTc lengthening.…”
Section: Discussionmentioning
confidence: 53%
“…In the skeletal muscle of other animal species such as cats (Minneman et al, 1979), cattle (Ijzerman et al, 1984), guinea pigs (Elfellah & Reid, 1987b) and rabbits ) the ,-adrenoceptors are exclusively of the 02-adrenoceptor subtype. The presence of 32-adrenoceptor binding sites on membranes together with the large pool of potassium which is within skeletal muscle is consistent with the involvement of these receptors in short term regulation of plasma potassium (Lockwood & Lum, 1974;Clausen & Flatman, 1980;Struthers et al, 1983;Brown et al, 1983). The density and affinity of the receptors for ICYP in both rectus abdominis and vastus lateralis muscles were similar, suggesting the former was representative of skeletal muscle in man.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore 3-adrenoceptors in skeletal muscle have been suggested to maintain physiological concentrations of potassium in plasma especially during exercise and stress and also to mediate the hypokalaemic response to P2-adrenoceptor agonists in animals and man (Lockwood & Lum, 1974;Brown et al, 1983;Struthers et al, 1983;Brown, 1985;Williams etal., 1985;Haalboom et al, 1985;Elfellah & Reid, 1987a). Recent studies have shown that in various animal species the skeletal muscle 3-adrenoceptors are of the 32-subtype (Minneman et al, 1979;Ijzerman et al, 1984;Elfellah & Reid, 1987b).…”
Section: Introductionmentioning
confidence: 99%
“…A lower dose infusion in man produces hypokalaemia with no initial hyperkalaemia (Struthers et al, 1983).…”
Section: Potassiummentioning
confidence: 99%